Sowing dates for early lentil cultivars in four regions of Minas Gerais, Brazil - Vieira, Rogério Faria (1999)
Trials were conducted in five municipalities of four regions of Minas Gerais State: Viçosa, Leopoldina (Zona da Mata), Patos de Minas (Alto Paranaíba), Uberaba (Triângulo) and Janaúba (Norte), in order to determine the best sowing date for early lentil. In Viçosa, six sowing dates were studied from 15th March to 30th May; in Leopoldina, four, from 7th April to 10th June; in Uberaba and Patos de Minas, six, from 17th February to 2nd June; in Janaúba, five, from 16th May to 3rd August. The interval between sowing dates was approximately 20 days. The cultivar Precoz planted with 30 seeds per meter and 40 cm between rows was used in the Viçosa trial. The cultivar Silvina with 50 seeds per meter and 30 cm between rows was used in the other trials. All trials were sprinkler irrigated. In general the highest yields were obtained when lentil was planted in May, particularly in the second half. In Viçosa, lentil also performed well when planted during the second half of March. In Leopoldina and Janaúba, the warmest locations, planting at the beginning of June did not impair lentil yield. From emergence to flowering, lentil took between 28 to 60 days, and from emergence to harvest, between 92 to 112 days, when planted during the best sowing dates. The highest yield was attained at Leopoldina when lentil was planted on 27 May: 1,644 kg/ha. One hundred-seed weight of cultivar Silvina varied from 5.5 to 6.3 grams when lentil was planted in May.